Young children’s motor skill development in outdoor experiences - Nonis, Karen; Yee, J. (2010)
© 2010 by World Scientific Publishing Co. Pte. Ltd. All rights reserved.Many studies show how physical activities can affect fundamental motor skills as well as how fundamental motor performance can also influence the participation of sports and physical activities. Parents’ and/or guardians’ perception of motor skills development is equally important for the interest and participation in sports and physical activities by young children. This chapter provides an overview of the development of motor skills of young children in the Asia-Pacific region with a focus on recent research in Singapore. A portion of the paper addresses research on preference and performance, and how these affect young children’s motor performance. The importance of outdoor physical experiences and the constraints of space, and the implications for children’s sports and physical experiences in Singapore are discussed.